The Category of Generation in Polish Linguistic Studies (Current Status and Perspectives) - Ruszkowski, Marek (Respectus Philologicus, 2015)
In linguistic studies, a generation is understood as “a group of people who are more or less the same age (Dubisz red. 2003, t. 3: 298 )”. It is assumed that the linguistic memory, the knowledge of linguistic conventions, the ability to take notice of nuances in one’s language is the only and unique cultural heritage that is difficult to learn and is passed from generation to generation, albeit with smaller or bigger modifications. Such modifications are the reason why the language is differentiated in generational terms, and it is the age that plays the principal role in that differentiation. Apart from the biological criterion, the geographic one, that is the area of a specific region, determinates the distinct features in the speech of generations. The analysis of differences in speech of generations allows determining the direction, nature, pace, mechanism of and reasons for linguistic changes. Generally, scientists focus on phonetic, lexical, and morphological differences shown in the language spoken by people from different generations. In Poland, the studies of differences in the speech of generations are at an introductory stage. The reconnaissance of the research area has been carried out, and basic determinations have been made, but the scope of analysis seems to be too narrow. A research perspective would be to use the quantitative indicators that are showing now and will show in the future that the common sense assumptions about specific frequency ratios between parts of speech, an increase in complexity of utterances and their lexical wealth concurrent with age does not need to be corroborated by empirical research. It is also advisable to analyse the differences in speech of one generation, especially the medium-age or old-age generation, in terms of sex, education, living, and other possible parameters. It will give the answer to the question to what extent the speech of people from a specific generation is a linguistic monolith, and to what extent it is a collection of idiolects.